Research areas and trends in family-centered care in the 21st century: a bibliometric review - Hriberšek, Mojca; Eibensteiner, Fabian; Bukowski, Nils; Yeung, Andy Wai Kan; Atanasov, Atanas G.; Schaden, Eva (Frontiers in Medicine, 2024)
This review aims to present an overview of impactful publications, authors, institutions, journals, countries, fields of application and trends of FCC in the 21 st century as well as suggestions on further research.The Web of Science Database was searched for publications on FCC between January 2000 and Dezember 2023. After screening for duplicates, VOS Viewer and CiteSpace were used to analyze and visualize the data.Family-centered care in the 21 st century 2 Scientific interest in FCC has grown and resulted in the scientific output of 4836 publications originating from 103 different countries. Based on the frequent author keywords, FCC was of greatest interest in neonatology and pediatrics, nursing, critical and intensive care, end-of-life and palliative care, and patient-related outcomes. The recent research hotspots are "patient engagement", "qualitative study", and "health literacy".FCC has gained recognition and spread from the pediatric to the adult palliative, intensive, endof-life and geriatric care settings. This is a very reassuring development since adults, especially when older, want and need the assistance of their social support systems. Recent research directions include the involvement of patients in the development of FCC strategies, health literacy interventions and the uptake of telemedicine solutions.